The Effects of Climate Change on GDP by Country and the Global Economic Gains From Complying With the Paris Climate Accord - Kompas, Tom; Pham, Van Ha; Che, Tuong Nhu (Earth's future, 2018)
Computable general equilibrium (CGE) models are a standard tool for policy analysis and forecasts of economic growth. Unfortunately, due to computational constraints, many CGE models are dimensionally small, aggregating countries into an often limited set of regions or using assumptions such as static price‐level expectations, where next period's price is conditional only on current or past prices. This is a concern for climate change modeling, since the effects of global warming by country, in a fully disaggregated and global trade model, are needed, and the known future effects of global warming should be included in forward‐looking forecasts for prices and profitability. This work extends a large dimensional intertemporal CGE trade model to account for the various effects of global warming (e.g., loss in agricultural productivity, sea level rise, and health effects) on Gross Domestic Product (GDP) growth and levels for 139 countries, by decade and over the long term, where producers look forward and adjust price expectations and capital stocks to account for future climate effects. The potential economic gains from complying with the Paris Accord are also estimated, showing that even with a limited set of possible damages from global warming, these gains are substantial. For example, with the comparative case of Representative Concentration Pathway 8.5 (4°C), the global gains from complying with the 2°C target (Representative Concentration Pathway 4.5) are approximately US$17,489 billion per year in the long run (year 2100). The relative damages from not complying to Sub‐Sahara Africa, India, and Southeast Asia, across all temperature ranges, are especially severe. Plain Language Summary This work shows considerable global economic gains from complying with the Paris Climate Accord for 139 countries. For example, with the comparative case of a temperature increase of four degrees, the global gains from complying with the 2° target are approximately US$17,489 billion per year in the long run (year 2100). The relative damages from not complying to Sub‐Sahara Africa, India, and Southeast Asia are especially severe. Key Points The global economic gains from complying with the Paris Climate Accord are shown to be substantial across 139 countries With the comparative case of RCP8.5 (4°C), the global gains from complying with the 2°C target (RCP4.5) are US$17,489 billion per year The relative damages from not complying with the 2°C target to Sub‐Sahara Africa, India, and Southeast Asia are especially severe